FOOD IMPORT REGULATION IN RUSSIA IN THE CONDITIONS OF SANCTIONS - M. V. Mintusov (Вестник университета)
Since the beginning of introduction of the anti-Russian sanctions problems of regulation of food import became aggravated. Consequences of imposition of sanctions for the Russian food market are analyzed in the article. The directions of state regulation of import in the conditions of sanctions are designated.